2020
DOI: 10.7758/rsf.2020.6.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Competing Public and Private Television Advertising Campaigns and Marketplace Enrollment for 2015 to 2018

Abstract: The Affordable Care Act was a landmark political achievement in reforming the American health insurance system but has been subject to considerable political pressure. Administrative actions, such as eliminating federal advertising, have served as a replacement for failed legislative repeal efforts. We use a county-level fixed-effects model with data for thirty-four states for the 2015 to 2018 open enrollment periods to measure dose-response relationships between health insurance and health-care-related politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…Funding Cuts to the ACA Navigator Program and Privately Sponsored Television Advertising people in marketplace coverage, advertising may be a substitute for public funding of the navigator program, albeit an imperfect one. Despite evidence of the association between outreach and health insurance enrollment, including direct enrollment assistance via navigators 25,[34][35][36] and television advertising, 16,24,[37][38][39][40] little research has explored the interplay between public and private sector sources of outreach. To assess the repercussions of recent developments and inform policy decisions, this study examined the association between the Trump-era cuts in navigator program funding and the volume of private sector advertising.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
See 3 more Smart Citations
“…Funding Cuts to the ACA Navigator Program and Privately Sponsored Television Advertising people in marketplace coverage, advertising may be a substitute for public funding of the navigator program, albeit an imperfect one. Despite evidence of the association between outreach and health insurance enrollment, including direct enrollment assistance via navigators 25,[34][35][36] and television advertising, 16,24,[37][38][39][40] little research has explored the interplay between public and private sector sources of outreach. To assess the repercussions of recent developments and inform policy decisions, this study examined the association between the Trump-era cuts in navigator program funding and the volume of private sector advertising.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…We used a method described in previous work to categorize advertisements by whether they were privately sponsored and by product category (Medicare, Medicaid, and private non-Medicare, non-Medicaid; the final category included marketplace, non-ACA-compliant plans, and employer-sponsored coverage). 16 In addition, advertisements were categorized according to the open enrollment period in which they aired. Open enrollment periods begin in the autumn before the plan year, which starts on January 1, and end either in the December before the plan year or at some point early in the plan year.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, research examining the first open-enrollment period of the ACA (2013–2014) identified aggregate associations between the volume of insurance ads aired on TV to county-level insurance gains generally and Medicaid enrollment gains in particular (Karaca-Mandic et al, 2017); at the individual level, higher volumes of advertising exposure were also associated with insurance-related outcomes in 2014 (Gollust, Wilcock, et al, 2018). Subsequent research examining county-level Marketplace enrollment data for the 2015 through 2018 open enrollment periods showed a statistically significant relationship between insurance enrollment and airings of advertisements by state sponsors in particular (Shafer et al, 2020). Another study examining discontinuities in advertising between media markets also found relationships between advertising and enrollment, but these relationships differed based on sponsor type (state or federal government vs. private companies; Aizawa & Kim, 2020).…”
Section: Introductionmentioning
confidence: 99%